The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.7759/cureus.12548
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Near-Miss as a Surrogate Indicator of the Quality of Obstetric Care: A Study in a Tertiary Care Hospital in Eastern India

Abstract: Background Monitoring severe acute maternal morbidity or maternal near-miss is currently proposed by WHO as a valuable tool to assess the quality of obstetric care and implement new strategies for improving maternal health. Aim and objective The objective of this study was to assess and analyze the incidence of maternal near-miss (MNM) and maternal death (MD) at Tata Main Hospital, Jamshedpur, a tertiary care hospital in eastern India. Material and method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
3
6
1
Order By: Relevance
“…In the present study, the mean age of near-miss cases and maternal death are comparable to study of Kalra et al 13 . Our results are consistent with the study of Vinita Singh et al 14 who found maximum near misses in the 20-24 years of age group while the minimum number of women was in the age range of >35years.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the mean age of near-miss cases and maternal death are comparable to study of Kalra et al 13 . Our results are consistent with the study of Vinita Singh et al 14 who found maximum near misses in the 20-24 years of age group while the minimum number of women was in the age range of >35years.…”
Section: Discussionsupporting
confidence: 93%
“…MMR was evaluated per 100,000 live births, whereas MNMR was evaluated using 1,000 live births as the denominator. Oladapo, et al 26 , and Akpan, et al 27 MM Ratio is reported lower than our study by Shaheen, et al 13 , Shahid, et al 15 , Aziz, et al 16 , Roopa, et al 19 , Singh, et al 20 , Kansara, et al 22 , Dhingra, et al 23 , Heemelaar, et al 25 , Chikadaya, et al 28 , David, et al 29 and Lotufo, et al 30 The caliber of maternal health care is illustrated by obstetric death. In our part of the world the near-misses are not usually used as a measure of the obstetric quality care as is also not used in many regions having increased MMR.…”
Section: Data Analysis Plancontrasting
confidence: 52%
“…The pooled prevalence of maternal near miss from 13 studies (about 378,173 study participants) indicated 14% [95% CI: 8, 19]. This finding was greater than the global weighted pooled burden of maternal near misses [ 52 ], a study done in sub-Saharan Africa, Europe and Northern America [ 53 ], a study done in Tanzania [ 13 ], Latin America [ 54 ], Kenya [ 11 ], Harare, Namibia [ 55 ], Zimbabwe [ 56 ], South Africa [ 57 ], Eastern India [ 58 ] and Rwanda [ 59 ]. The reason for this variation could be the scope of the study, the year of publication, and the nature of the variation of MNM among high and low-income countries.…”
Section: Discussionmentioning
confidence: 99%